Does the Wage Tax System cause Budget Deficits? - Arno Riedl; Frans A.A.M. van Winden (Tinbergen Institute, 2000)
In this paper we investigate experimentally the functioning of a wage tax financed unemployment benefit system on the development of the budget deficit, unemployment, and some other indicators of economic performance in an international economy. We find support for the hypothesis that out-of-equilibrium price uncertainty affects the behavior of economic agents. Dueto uncertainty about prices risk-averse producers are hypothesized to be reluctant to employ inputs with the additional effect of too low wages and too high output prices. Our results support this hypothesis of a `risk-compensated price-mechanism'. We also find that the downward pressure on wages is exacerbated by an over-supply of labor by consumers. These observationscan explain the budget deficits we observe in the laboratory economies. Furthermore, we find that tax adjustments in order to facilitate a balancing of the budget has strong adverse effects on unemployment and real GDP.
Keywords: C90; D21; D51; D60; E62; H2; H62; 330; Budget deficit; experiment; price uncertainty; unemployment benefit; wage tax; Arbeitslosenversicherung; Lohnsteuer; Haushaltsdefizit; Theorie